Excitation-emission matrices produced by custom-built high-pressure cuvette system - Maria Papadimitraki; Urban Wünsch; Ronnie N Glud (PANGAEA, 2025)
A custom high-pressure cuvette system was developed, capable of operating at pressures up to 110 MPa to investigate pressure-dependent effects on enzymatic activity and biogeochemical element cycling in the deep ocean. This system features three sapphire windows for real-time absorption and fluorescence measurements, as well as temperature control. This dataset contains the maximum-normalized fluorescence measurements obtained using this system, for assessing the enzymatic activity of extracellular chitinase produced by a piezo-sensitive Vibrio anguillarum (PF430-3, originally isolated in Chile) strain. Specifically, the dataset includes excitation-emission matrices (EEMs) for the substrate 4-MUF-NAG, the fluorophore 4-MUF and the combined signal from 4-MUF-NAG in 30% medium along with cleaved 4-MUF in the presence of chitinase enzymes.